Evaluation of genetic diversity and relationships among natural populations of Boenninghausenia albiflora Rchb. ex Meisn. using RAPD profiling - Dixit, A.=700 1 Singh, S.; Singh, N.K.; Garg, G.K.
(En, Fr, Es)
Ilus., 14 ref.
Keywords: POBLACION VEGETAL; VARIACION GENETICA; RAPD; ITALIA; BOENNINGHAUSENIA ALBIFLORA